Goldstone Apple Valley Radio Telescope Monitoring Flux Density of Jupiter's Synchrotron Radiation during the Juno Mission. (16th September 2020) - Velusamy, T.; Adumitroaie, V.; Arballo, J.; Levin, S. M.; Ries, P. A.; Dorcey, R.; Kreuser-Jenkins, N.; Leflang, J.; Jauncey, D.; Horiuchi, S.
Abstract: Goldstone Apple Valley Radio Telescope (GAVRT) is a science education partnership among NASA, the Jet Propulsion Laboratory (JPL), and the Lewis Center for Educational Research (LCER), offering unique opportunities for K-12 students and their teachers. As part of a long-term Jupiter synchrotron radiation (JSR) flux density monitoring program, LCER has been carrying out Jupiter observations with some student participation. In this paper we present the results of processed data sets observed between 2015 March 6 and 2018 April 6. The data are divided into 5 epochs, grouped by time and by Jupiter's ephemeris parameters as observed from Earth. We derive JSR beaming curves at different epochs and Earth declinations. We present a comparison of the observed beaming curves with those derived from most recent models for the radiation belts. Our results show an increasing trend of the JSR flux density which seem consistent with the models for the magnetospheric solar wind interactions.